All Days 2011
DOI: 10.2118/144468-ms
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Integrated Solutions for Reservoir Management: San Joaquin Valley Case Study

Abstract: To achieve more efficient business processes by exploiting data and knowledge management, real-time systems and advanced analytical tools, most major integrated and service companies have developed, or are in the process of developing, intelligent programs also known as Digital Oil Field of the Future 3 . The i-field TM program represents Chevron's efforts to integrate people, processes, technology and information to achieve its vision of Upstream Transformation. Ultimately, this vision translates to higher-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Similar study by Chevron reported the case of its Kern River field with 9,000 active wells that records 1,000,000 data points daily [19]. While large fraction of Chevron's data is in structured form, the rest is hidden in Microsoft Excel and Microsoft Access files on individual users' desktop that accounts for 70% of the knowledge value.…”
Section: Related Workmentioning
confidence: 71%
See 2 more Smart Citations
“…Similar study by Chevron reported the case of its Kern River field with 9,000 active wells that records 1,000,000 data points daily [19]. While large fraction of Chevron's data is in structured form, the rest is hidden in Microsoft Excel and Microsoft Access files on individual users' desktop that accounts for 70% of the knowledge value.…”
Section: Related Workmentioning
confidence: 71%
“…Data curation problem and potential solutions have also been documented by E&P organizations [1], [19]. Most efforts towards digital oil field vision addressed data management and curation issues in some form or the other.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploration and production (E&P) life cycle includes data intensive activities like seismic data acquisition, geologic interpretation, modeling, reservoir analysis, drilling target selection, drilling, well logging and analysis, production and well monitoring that links the oil field measurements to oil field management decisions [2]. Illustrating the data intensive nature of one of these activities, a study by Chevron reported the case of its Kern River field with 9,000 active wells that records 1,000,000 data points on daily basis [19]. While large fraction of Chevron's data is in structured form, the rest is hidden in Microsoft Excel and Microsoft Access files on individual users' desktop that accounts for 70% of the knowledge value.…”
Section: Introductionmentioning
confidence: 99%